Vauxiids as descendants of archaeocyaths: a hypothesis. (9th June 2021) - Luo, Cui; Yang, Aihua; Zhuravlev, Andrey Yu.; Reitner, Joachim
Abstract : Archaeocyaths were one of the major animal groups contributing to the Cambrian Explosion. Despite an overall poriferan appearance of their hypercalcified skeletons, they exhibit a number of peculiar features such as the presence of septa and an absence of spicules. This sets archaeocyaths apart from general trends in early poriferan evolution. Fossils recently discovered from the early Cambrian Guanshan Lagerstätte of South China exhibit features typical for the suborder Archaeocyathina whilst possessing a silicified skeleton associated with carbonaceous material. This rigid fibrous skeletal framework, on the other hand, fits the diagnosis of the supposed ancestral aspiculate demosponges, the family Vauxiidae. By a detailed description of this specimen and a direct morphological comparison between the Archaeocyathina and the Vauxiidae, we suggest that the supposed Cambrian representatives of horny demosponges, that is, vauxiids, probably, were a progeny lineage of archaeocyathines. They survived the extinction of hypercalcified archaeocyaths due to their ecological adaption to siliciclastic environments. The existence of hypercalcified dictyoceratid ('keratosan') sponge Vaceletia, well known as a 'living archaeocyath', supports such a possibility.